Anatomical Description of Zygomatic Foramina in African American Skulls. Issue 2 (March 2018) - Zhao, Yue; Chundury, Rao V.; Blandford, Alexander D.; Perry, Julian D.
Abstract : Purpose: The zygomaticofacial/temporal/orbital nerve is a terminal branch of the zygomatic nerve and exits the orbit through zygomatic foramina. The nomenclature in the literature varies with some studies identifying all 3 foramina on the malar surface of the zygoma, while others describe each along different aspects of the zygoma. In this study, foramen on the malar surface of the zygoma is termed zygomatic foramen, and the authors describe anatomical variations in the position and number of these foramina in an African American population. Methods: Sixty-two African American skulls from the Hamann-Todd collection of the Cleveland Museum of Natural History were studied. The primary outcome was the number of zygomatic foramina on the malar surface of the zygomatic bone. Secondary outcomes included the location of foramina relative to the orbital rim and the frontozygomatic suture. Mean and standard deviation were used to describe measurements. Chi-squared and Wilcoxon signed rank tests were used to analyze measurements between left and right hemicrania. Results: The average number of foramina was 1.98 ± 0.93. More foramina were found on the right (2.13 ± 0.98) when compared with the left (1.68 ± 0.79; p = 0.001). The average distance between the lateral-most and medial-most foramina was 9.7 ± 5.0 mm. The distance from the orbital rim to the lateral foramen was 8.4 ± 4.2 mm, and distance from the orbital rim to the medial foramen was 7.7 ± 2.1 mm. The frontozygomatic suture was 22.9 ± 3.9 mm from the lateral foramen and 27.9 ± 3.6 mm from the medial foramen. Conclusion: The locations of the foramina in relation to the frontozygomatic suture and orbital rim were consistent with other populations. However, in this African American population, more zygomatic foramina were noted compared with previously published results in Korean, Indian, Brazilian, and West Anatolian populations. Surgeons should be cognizant of zygomatic foramina in this population to reduce potential neurovascular complications. Abstract : In this study, the authors evaluated the number and anatomic variability of zygomatic foramina in African American skulls.